Evaluation of an innovative low flow oxygen blender system for global access - Ng, Ellie; Dundek, Michelle; Burke, Thomas F. (Frontiers in Pediatrics, 2022)
Background: Safe and effective oxygen delivery methods are not available for the majority of infants and young children globally. A novel oxygen blender system was designed to accurately deliver concentration-controlled, oxygen-enriched air to hypoxemic children up to age five. The system does not require compressed medical air, is compatible with both oxygen tanks and oxygen concentrators, and is low cost. This is the first study that tested the performance of the innovative oxygen blender system. Methods: The performance of the oxygen blender system was assessed in vitro based on delivered oxygen levels and flow rates with an oxygen tank, an oxygen tank using a nasal occlusion model, and an oxygen concentrator. Results: The measured %O2 of the performance test was within ±5% of full scale (FS) of the target value across all flows and all nasal cannulas. Occlusion testing demonstrated that 50% occlusion did not significantly affect the system outputs. The oxygen blender system was shown to be compatible with both oxygen tanks and oxygen concentrators. Conclusions: The novel oxygen blender system accurately controls oxygen concentrations and blended air flow rates, and is compatible with both oxygen tanks and oxygen concentrators. This innovation may be an opportunity for improved infant and child oxygen treatment worldwide.